2012
DOI: 10.4314/thrb.v13i5.5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal health in fifty years of Tanzania independence: Challenges and opportunities of reducing maternal mortality

Abstract: High rate of maternal death is one of the major public health concerns in Tanzania. Most of maternal deaths are caused by factors attributed to pregnancy, childbirth and poor quality of health services. More than 80% of maternal deaths can be prevented if pregnant women access essential maternity care and assured of skilled attendance at childbirth as well as emergency obstetric care. The objective of this review was to analyse maternal mortality situation in Tanzania during the past 50 years and to identify e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 14 publications
0
60
0
1
Order By: Relevance
“…Majority of the pregnant women in the present study 54% reported to have two visit of ANC from their previous pregnancy and about 15.4% only reported to have 4 visits of ANC visits. This observation gives a promising future to attain the Focused Antenatal Care campaign failure to reach a goal of at least 80% visit coverage in pregnant women [20].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Majority of the pregnant women in the present study 54% reported to have two visit of ANC from their previous pregnancy and about 15.4% only reported to have 4 visits of ANC visits. This observation gives a promising future to attain the Focused Antenatal Care campaign failure to reach a goal of at least 80% visit coverage in pregnant women [20].…”
Section: Discussionmentioning
confidence: 51%
“…However, the initiation of the program of ANC services requires good knowledge and awareness of appropriate preventive measures among the general public to ensure positive health behavior changes and reproductive health seeking habits in both partners [15].…”
Section: Discussionmentioning
confidence: 99%
“…Those challenges were; accessibility of maternal health care services is still inadequate particularly in rural and underserved areas, inadequate quality of health services provided by the health care system, the government budget allocation for health sector and inadequate numbers of skilled health workers, and still those available are unevenly distributed [3]. The another study conducted in Ethiopia reflected that Sociodemographics, socio-economic, socio-cultural and personal factors are also another challenges that decrease the communities' utilizations of maternal health care services [10].…”
Section: The Challenges On Maternal Health Services Provision From Gomentioning
confidence: 99%
“…More than 80% of maternal deaths can be prevented if pregnant women access essential maternity care like antenatal care, institutional delivery, postnatal care and assured of skilled attendance at childbirth as well as emergency obstetric care [3].…”
mentioning
confidence: 99%
“…Most are caused by factors attributed to delays in seeking care, lack of skilled birth attendants, and poor quality of health services [4–7]. More than 80% of deaths can be prevented if pregnant women access essential maternity care and are attended by a skilled provider at childbirth [2, 8, 9]. …”
Section: Introductionmentioning
confidence: 99%